Impact Loading During Distracted Running Before and After Auditory Gait Retraining - Ching, Eric; An, Winko Wen-Kang; Au, Ivan Pui Hung; Zhang, Janet Hanwen; Chan, Zoe Y.S.; Shum, Gary; Cheung, Roy T.H. (International Journal of Sports Medicine, 2018)
Visual feedback gait retraining has been reported to successfully reduce impact loading in runners, even when the runners were distracted. However, auditory feedback is more feasible in real life application. Hence, this study compared the peak positive acceleration (PPA), vertical average (VALR) and instantaneous (VILR) loading rate during distracted running before and after a course of auditory feedback gait retraining in 16 runners. The runners were asked to land with softer footfalls with and without auditory feedback. Low or high sound pitch was generated according to the impact of particular footfall, when compared with the preset target. Runners then received a course of auditory gait retraining, and after the gait retraining, runners completed a reassessment. Runners before gait retraining exhibited lower PPA, VALR and VILR with augmented auditory feedback (p<0.049). We found a reduction in PPA, VALR and VILR after gait retraining, regardless of the presence of feedback (p<0.018). However, runners after gait retraining did not demonstrate further reduction in PPA and VALR with auditory feedback (p>0.104). A small effect of auditory feedback on VILR in runners after gait retraining was observed (p=0.032). Real time auditory feedback gait retraining is effective in impact loading reduction, even when the runners were distracted.
Keywords: wearable sensor; accelerometer; vertical loading rate; dual task; kinetics